Hanging latrines: far away from functional latrines within the very heart of an urban centre - Saha Shyantani (2022)
A conference contribution for the 1st Water-WISER Early Career Researcher Conference, Transdisciplinary Global Perspectives on Water and Waste Services, held at Loughborough University 21 - 23 June 2022.